Influenza: under complications and management, mention needs to be made of secondary bacterial infection and its treatment - Bari, Mohammed Abdulmuttalib Abdul (International Journal of Basic & Clinical Pharmacology, 2025)
This review explains the complications and the management of influenza, focusing on their secondary bacterial infections. It outlines the types of influenza viruses, transmission, and vaccination. It outlines the different secondary infections that may arise after an influenza infection; hence, one considers the bacterial, fungal, and viral infections. It emphasizes the need for timely diagnosis and proper management, which would involve the use of antibiotics, antifungal agents, or antiviral drugs depending on the infection. It further advises on prevention techniques, which involve vaccination and proper hygiene of hands to avert the incidence of secondary infection. From the discussion above, this document has identified a wide précised account of the complications and management approaches with influenza and its complicating secondary infections.